2021
DOI: 10.1002/cam4.4359
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N‐methyltransferase is related to MELF pattern invasion in endometrioid carcinoma

Abstract: Grade 1 (G1) endometrioid carcinoma (EC) is relatively a good prognosis. However, in a minority of cases, G1 shows an aggressive histological pattern known as the microcystic, elongated, and fragmented (MELF) pattern. We previously reported that EC with high expression levels of S100A4 and serum deprivation‐response protein (SDPR) was related to MELF pattern invasion. However, the molecular features of the invasive front area of the MELF pattern have not been investigated. In this study, we searched for genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This association of MELF pattern with wild-type CTNNB1 has been previously reported, and the absence of MELF pattern was even suggested as one the most sensitive predictors of CTNNB1 mutation [36]. In another recent study by Tahara et al [37], nicotinamide N-methyltransferase (NNMT) was found to be related to MELF pattern in EEC and promotes cell migration and invasion via the suppression of H3K9me2 methylation. They speculated that on the invasive tumor front, the elevated expression of NNMT might contribute to the characteristic morphology of MELF through the suppression of H3K9me2 followed by the enhancement of various pathways related to cell migration and invasion [37].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This association of MELF pattern with wild-type CTNNB1 has been previously reported, and the absence of MELF pattern was even suggested as one the most sensitive predictors of CTNNB1 mutation [36]. In another recent study by Tahara et al [37], nicotinamide N-methyltransferase (NNMT) was found to be related to MELF pattern in EEC and promotes cell migration and invasion via the suppression of H3K9me2 methylation. They speculated that on the invasive tumor front, the elevated expression of NNMT might contribute to the characteristic morphology of MELF through the suppression of H3K9me2 followed by the enhancement of various pathways related to cell migration and invasion [37].…”
Section: Discussionsupporting
confidence: 63%
“…Tahara et al [44] documented that the programmed cell death-ligand 1 (PD-L1) protein was strongly expressed in both the tumor cells and immune cells at the invasive front of grade 1 EEC showing MELF pattern, suggesting a possible therapeutic role for targeting programmed cell death 1/PD-L1 axis in EEC. They also reported the link between a high expression of S100A4 [45], serum deprivation-response protein (SDPR) [46], and NNMT [37] with MELF pattern. They demonstrated not only that high S100A4 expression contributes to an aggressive phenotype of EEC, but also that its elevated expression is closely related to MELF pattern.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Among them, S100A4 has specialized histological features of endometroid carcinoma, including the microcystic, elongated, and fragmented (MELF) pattern. 54,55 Usually, well-differentiated uterine endometrioid carcinomas are less likely to metastasize, but those with the MELF feature tend to metastasize to the lymph nodes. Endometrioid carcinomas with the MELF feature showed high S100A4 expression and invasive phenotype, suggesting that the invasive character of ALDH1A1-hi cells may be partly due to the high expression of S100A4.…”
Section: Introductionmentioning
confidence: 99%
“… 50–53 Immunohistochemical results for SDPR and S100A4 in endometrioid carcinoma are shown in Figure 3. Among them, S100A4 has specialized histological features of endometroid carcinoma, including the microcystic, elongated, and fragmented (MELF) pattern 54,55 . Usually, well‐differentiated uterine endometrioid carcinomas are less likely to metastasize, but those with the MELF feature tend to metastasize to the lymph nodes.…”
Section: Introductionmentioning
confidence: 99%